Glial endozepines and energy balance: Old peptides with new tricks. Issue 5 (26th October 2020) - Lebrun, Bruno; Barbot, Manon; Tonon, Marie‐Christine; Prévot, Vincent; Leprince, Jérôme; Troadec, Jean‐Denis
Abstract: The contribution of neuroglial interactions to the regulation of energy balance has gained increasing acceptance in recent years. In this context, endozepines, endogenous analogs of benzodiazepine derived from diazepam‐binding inhibitor, are now emerging as major players. Produced by glial cells (astrocytes and tanycytes), endozepines have been known for two decades to exert potent anorexigenic effects by acting at the hypothalamic level. However, it is only recently that their modes of action, including the mechanisms by which they modulate energy metabolism, have begun to be elucidated. The data available today are abundant, significant, and sometimes contradictory, revealing a much more complex regulation than initially expected. Several mechanisms of action of endozepines seem to coexist at the central level, particularly in the hypothalamus. The brainstem has also recently emerged as a potential site of action for endozepines. In addition to their central anorexigenic effects, endozepines may also display peripheral effects promoting orexigenic actions, adding to their complexity and raising yet more questions. In this review, we attempt to provide an overview of our current knowledge in this rapidly evolving field and to pinpoint questions that remain unanswered. Main Points: Glial endozepines expression is modulated by metabolic signals. Endozepines were reported to exert anorexigenic effect by acting at the hypothalamus level. Recent developments reveal a complex and multifaceted mode of action.